An aggregation-induced emission (AIE) fluorescent chemosensor for the detection of Al(III) in aqueous solution. (December 2019) - Li, Yuanyuan; Xu, Kui; Si, Yue; Yang, Cuiping; Peng, Qiuchen; He, Juan; Hu, Qinggang; Li, Kai
Abstract: A novel fluorescent chemosensor (2 ) for the detection of Al(III) was designed based on the strategy of aggregation-induced emission (AIE), which was synthesized by introducing carboxyl group to tetraphenylethylene structure.2 can bind with Al(III) to form chelate polymers with AIE characteristic, giving rise to an intense "turn-on" response in aqueous solution at pH 7.0. The binding stoichiometry of2 toward Al(III) was in 1:1. High sensitivity and selectivity to Al(III) were achieved. A detection limit of 1.96 μmol L −1 and a linear rang of 0.0–50.0 μmol L −1 were obtained. Furthermore, 2 was successfully applied in detecting Al(III) in real water samples, which showed satisfactory recovery and accuracy. Graphical abstract: Image 1 Highlights: A new tetraphenylethylene (TPE) derivative was prepared for sensing Al(III). The chemosensor exhibited fluorescence "turn-on" response to Al(III). The detection can be performed in neutral aqueous solution. Chelate polymers with AIE character was formed by the chemosensor and Al(III). Fast & highly selective detection of Al(III) in real water samples was achieved.